Pemikiran Al-Syatibi Dalam Bidang Ekonomi - Suharyono; Kurniawan, Septian (El-kahfi | Jurnal Ekonomi Islam, 2022)
This study was discusses the thoughts of Al-Syatibi in the economic study. Al-Syatibi was a Muslim scholar who studied the concept of maqasid sharia especially in the area of ​​economics. This study used qualitative analysis using reference to previous studies sourced from scientific literature. The study of Maqasid Syariah, about consumer behavior and policies both individually and the government was one of the studies of AL-Syatibi.The conclusion, Al-Syatibi's thoughts in the field of economics focus on economic activities oriented to benefit.